The long-term effect of biochar application to Vitis vinifera L. reduces fibrous and pioneer root production and increases their turnover rate in the upper soil layers - Beatrice, Peter; Dalle Fratte, Michele; Baronti, Silvia; Miali, Alessio; Genesio, Lorenzo; Vaccari, Francesco Primo; Cerabolini, Bruno E. L.; Montagnoli, Antonio (Frontiers in Plant Science, 2024)
Fibrous and pioneer roots are essential in the uptake and transport of water and nutrients from the soil. Their dynamic may be influenced by the changing of soil physicochemical properties due to the addition of biochar, which, in turn, has been shown to improve plant growth and productivity in the short term. However, the long-term effects of biochar application on root dynamics are still widely unknown. In this study, we aimed to investigate the long-term effects of biochar application on grapevine fibrous and pioneer root dynamics and morphological traits in relation to soil characteristics. To this aim, grapevine plants amended in 2009 and 2010 respectively with one and two doses of biochar, were analyzed in their fibrous and pioneer root production and turnover rate, standing biomass, length, and specific root length, over two growing seasons. Our findings demonstrate that in the long term, biochar application significantly increased soil pH, nutrient availability, and water-holding capacity causing a decrease in the production of fibrous and pioneer roots which is reflected in a reduction of the root web characterized though by a higher turnover rate. Furthermore, we observed that these root morpho-dynamical changes were of higher magnitude in the upper soil layers (0-20 cm) and, at least in the long term, with no significant difference between the two doses. These results suggest that in the long term, biochar can be a powerful tool for improving soil quality, which in turn lowers carbon-cost investment toward the root production and maintenance of a reduced root web that might be directed into grapevine growth and productivity. Such effects shed some light on the root plastic and functional adaptation to modified soil conditions facilitated by the long-term application of biochar, which can be used for implementing adaptive agricultural practices to face the current climate change in a frame of sustainable agricultural policies.